Cracking Modeling In Partially Saturated Media With Phase-Field Method And Application To Rainfall-Induced Landslides. Issue 6 (October 2021) - Wang, Meng; Shao, Jian-Fu; Yu, Zhan
Abstract: Cracking is the principal mechanics of failure in engineering structures and geo-logical systems. Complex cracking patterns are observed in rock-like materials under compressive stresses. On the other hand, rainfall is one of the main triggering factors of landslides. Therefore, the rainfall induced landslides should be investigated by considering complex relationships between rainfall and rising groundwater table and related reduction of shear strength. In this paper, we present a new phase-field method for modeling the transition from diffuse damage to localized cracks. The damage variable is assumed to be driven by the deviatoric strain and positive (or dilatant) volumetric strain. This allows the description of tensile, shear and mixed cracks. The phase-field method is extended to partially saturated porous media by considering hydromechanical and phase-field coupling mechanisms. The proposed phase-field method is then applied to the analysis of rainfall-induced landslides in partially saturated conditions. The evolutions of pore water pressure, displacement and damage fields are predicted. Different failure mechanisms are discussed.